Some Italian-Croatian False Pairs in Restricted Collocations - Ljubičić, Maslina (2004)
In spite of the fact that formally similar and for the most part etymologically related lexical units agree semantically, they can disagree collocationally. Collocations are language-specific. This article deals with some Italian-Croatian false pairs in restricted collocations. Very often the Croatian follows German models. Strong contacts between languages are oriented towards the linguistic convergence on the lexical and phraseological level. Partial false pairs can become less partial, they can even become total pairs. The extreme case is that of the Italian duomo 'cathedral' and the Croatian dom 'home', which continue to have different meanings, but converge in the same technical collocation as a result of the paretymological reinterpretation of the French model dome 'dome' (it. cupola).
Projekt MZOS
ENG